2021
DOI: 10.2147/ijn.s323671
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal lncRNA CHL1-AS1 Derived from Peritoneal Macrophages Promotes the Progression of Endometriosis via the miR-610/MDM2 Axis

Abstract: Background Exosomes secreted by peritoneal macrophages (pMφ) are deeply involved in the development of endometriosis (EMs). Exosomes can mediate cell-to-cell communication by transferring biological molecules. This study aimed to explore the effect and mechanism of exosomal long non-coding RNA (lncRNA) CHL1-AS1 derived from pMφ on EMs. Materials and Methods Exosomes (exo) from pMφ were isolated, identified, and co-cultured with ectopic endometrial stromal cells (eESCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Endometriosis related EVs were isolated from peritoneal fluid [ 18 , 23 , 27 , 28 , 30 , 33 , 46 ], endometrium [ 18 20 , 25 , 28 , 29 , 34 , 35 , 37 , 38 , 41 , 42 , 44 , 47 ], endometriosis lesions [ 18 , 19 , 26 , 28 ], endometriomas [ 25 , 30 , 34 , 35 , 39 42 , 44 , 47 ], cervicovaginal swabs (in a single monkey) [ 32 ], plasma [ 18 , 31 ] and serum [ 18 , 26 , 28 , 31 , 34 36 , 39 , 43 , 45 , 47 ]. (Plasma is recommended by the ISEV over serum, due to the release of a significant amount of additional EVs from platelets during the clot formation when preparing serum [ 48 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometriosis related EVs were isolated from peritoneal fluid [ 18 , 23 , 27 , 28 , 30 , 33 , 46 ], endometrium [ 18 20 , 25 , 28 , 29 , 34 , 35 , 37 , 38 , 41 , 42 , 44 , 47 ], endometriosis lesions [ 18 , 19 , 26 , 28 ], endometriomas [ 25 , 30 , 34 , 35 , 39 42 , 44 , 47 ], cervicovaginal swabs (in a single monkey) [ 32 ], plasma [ 18 , 31 ] and serum [ 18 , 26 , 28 , 31 , 34 36 , 39 , 43 , 45 , 47 ]. (Plasma is recommended by the ISEV over serum, due to the release of a significant amount of additional EVs from platelets during the clot formation when preparing serum [ 48 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Control samples not clearly stated in methods Lee 2021 [ 27 ] Human ( n = 45) Human ( n = 45) Peritoneal fluid UC Partially Microbiota composition of EVs Not discussed, but potential diagnostic targets Not discussed Microbiome of peritoneal fluid and/or genital tract may influence development of endometriosis May be specific to women with endometrioma Li 2020 [ 28 ] Human (serum n = 48) Human (serum n = 21) CCM of ESCs from endometrium and endometriosis lesions, serum CCM: ExoQuick-TC Exosome Precipitation Solution (#EXOTC10A-1, SBI) Serum: SEC Yes VEGF-C Serum EV VEGF-C provided sensitivity of 81.3%, and specificity of 71.4% Potential therapeutic target (e.g. with levatinib) EV secreted VEGF-C induces lymphangiogenesis and pro inflammatory microenvironment to promote endometriosis progression Number of participant samples used for CCM EV assays unclear Li 2021 [ 29 ] Human ( n = 23) Mouse ( n = 18) Human ( n = 10) Mouse ( n = 9) CCM of M1 macrophages from endometrial biopsy UC Partially Not investigated Treatment of endometriosis with M1NVs (M1 macrophage derived EVs) safe in mouse model M1NVs inhibit angiogenesis, migration and invasion of endometriosis, via reprogramming of M2 macrophage phenotype EV cargo not investigated – mechanism of reprogramming unknown Liu 2021 [ 30 ] Human ( n = 50) Human ( n = 50) CCM of primary peritoneal macrophages isolated from peritoneal fluid UC …”
Section: Methodsmentioning
confidence: 99%
“…We found that thrombospondin 1 (Thbs1), tissue inhibitor of metalloproteinase 1 (Timp1), and cell adhesion molecule with homology to L1CAM (Chl1) were up-regulated in both the model and patients. These genes are known to play a role in cell adhesion and/or ECM organization, biological processes important for the attachment and invasion of ectopic cells in tissues [14][15][16]. Thus, these genes might be critical for the development of endometriosis via cell attachment and invasion in both model and patients.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of MDM2 was previously reported as a contributor to endometriosis progression by promoting proliferation, migration, and invasion and inhibiting apoptosis [ 25 ]. Another study by Liu et al revealed the axis linking MDM2 to endometriosis pathogenesis via miR-610 in the ectopic endometrial stromal cells, which introduced MDM2 as a potential therapeutic target for endometriosis [ 26 ]. The SLC6A8 gene is a creatine transporter that shows overexpression during the secretory phase in stromal cells and endometrial glands [ 27 ].…”
Section: Discussionmentioning
confidence: 99%